The EU's Shifting Borders Reconsidered: Externalisation, Constitutionalisation, and Administrative Integration - Evangelia Tsourdi; Andrea Ott; Zvezda Vankova (European Papers, 2022)
(Series Information) European Papers - A Journal on Law and Integration, 2022 7(1), 87-108 | Article | (Table of Contents) I. EU's shifting borders: an introduction. - II. Protecting borders and respecting human rights. - II.1. How to reconcile diverging constitutional objectives in light of hybridity and informality? - II.2. Which way forward with accountability? - III. EU's external borders: of administrative integration and the physical and legal infrastructures of deflection. - III.1. Hotspots as incubators of liminality and of an emerging European integrated administration. - III.2. Beyond hotspots: securitisation and deflection of "risky" migrants. - III.3. Screening, border asylum procedures, and streamlined returns: what's "new" in the new pact on migration and asylum? - IV. Overview of contributions. | (Abstract) Borders have gone far beyond their traditional static function of merely demarcating nation-states. Alongside physical border barriers, such as walls and barbwire fences, new technologies driven by sophisticated legal innovations have contributed to the multiplicity of border controls. These legal techniques have turned the border into an individualised moving barrier, conceptualized as a "shifting border" by Ayelet Shachar. Against this backdrop, this Article introduces, conceptually and thematically, the contributions to this Special Section which critically assess the paradigm of the shifting border in the EU and analyse its implications. We first map out intricate legal issues invoked by the rise of hybridity and informality in the EU's cooperation with third countries on migration and the resulting accountability deficit. Next, we scrutinize the physical and legal infrastructures of mobility regulation (and often deflection) that are currently employed at the EU's external territorial borders. We highlight the emergence of increasing horizontal (between the EU and national level) and vertical (across national levels) administrative integration as a prevailing mode of policy implementation at the EU's borders and reflect on the implications, including both challenges and opportunities, of this development. Finally, we scrutinise the Commission's proposals as part of a New Pact on Migration and Asylum with respect to the envisaged processes at the borders and the streamlining of external border control, asylum, and return in a seamless process finding that they create further risks for fundamental rights and procedural guarantees.